Magnet-related foreign body aspiration in two children requiring thoracotomy: A concerning report - Qalab Abbas; Amna Afzal Saeed; Muhammad Sarwar; Iraj Khan; Waris Ahmed; Nighat Sultana (Elsevier, 2022)
With the increase in use of smaller magnets in gadgets and toys at home, magnets pose a growing aspiration risk in children. We present two simultaneous cases of magnet-related foreign body aspiration (FBA) in two children, in two different cities: Karachi, and Lahore. They presented with similar signs and symptoms: tachypnea, tachycardia and asymmetric breath sounds on auscultation. They were initially diagnosed with the help of a chest X ray. Both the cases were complicated by failed bronchoscopy attempts due to the slippery texture of the magnet. Due to the failed bronchoscopy, both patients had a prolonged and complicated course including a 24-48 hour stay in the PICU prior to magnet removal. They eventually had to undergo thoracotomy for successful removal of the magnet. Both had an unremarkable post-operative course and were discharged in good health.